Perceptual impact of speech melody hybridization: English and Czech English - Volín, Jan; Poesová, Kristýna (Research in Language, 2016)
The current paper examines the role of intonation in the perception of foreign-accented speech. In order to assess how difficult it is to mentally process native, non-native and modified speech melodies, four conditions were analyzed and compared: native English, native English with Czech melody, Czech English with native melody and Czech English. The method of reaction times measurement in a word monitoring task was employed, in which 108 Czech listeners heard English sentences in the explored conditions and pressed a button when hearing a target word. Speech melody turned out to have a relatively weak but discernible impact on perceptual processing. Interestingly, Czech English proved to be more difficult to process than native English, although the listeners were Czech. The implementation of English F0 contours on Czech English speech slightly alleviated the cognitive load, however, the second hybrid, native English with Czech melody, pointed to the opposite direction. The causes of this discrepancy were investigated, particularly higher degrees of collocability in certain expressions.